Evaluation of dental implant osseointegration with resonance frequency analysis method: A retrospective study - Mehmet Gul; Halil Ibrahim Durmus (SRM Journal of Research in Dental Sciences, 2020)
Background/Aim: Dental implant stabilities are essential to prevent implant loss. The purpose of the study is to appraise the physical properties, bone density, and bone thickness of dental implants and the effects of the implant locations on stability. Materials and Methods: Thirty-six patients participated in the study at the Harran University Periodontology Department (between 2019 and 2020). Of these patients, 19 patients were female, 17 patients were male, and the average age of patients was 48.21 years. Patients who underwent dental implant surgery were contained in the study. A total of 127 dental implants were placed using standard surgical protocols. The specific transducer compatible with implant system was fixed to the implant body by means of an abutment using a screw. The implant stability quotient (ISQ, Osstell™) values were determined for each implant 4, 8, and 12 weeks after surgery. Results: As a result of the statistical analysis, the values of the ISQ taken in the mandible region were higher in the 4, 8, and 12 weeks compared to the values of the ISQ values obtained from the maxilla region. Statistically significant differences were also found between these values (P < 0.05). Conclusion: We found that implants with a long and wide width represented higher ISQ values and stability compared to shorter and narrower implants. Higher values were found in the mesiodistal direction compared to the buccolingual and buccopalatal directions, and in the mandible compared to the maxilla. This situation increases the stability in places where bone density and bone thickness are higher.